Fluid Abuse Following Minor to Intermediate Elective Surgeries - Hussein, Mohamad Theyab Hamad; Abdulkareem, Muqdad Fuad; Khalaf, Jalil I (Diyala Journal of Medicine, 2019)
Background: The restriction to the guidelines for postoperative management (as omission of routine use of nasogastric tubes, early institution of oral feeding and mobilization and clarified indications of administration of intravenous fluids) has resulted in a decrease in perioperative intravenous fluid administration in fast-track surgical programs (in particular day case surgeries). In minor to intermediate surgeries, shifting of perioperative fluids are small and organ dysfunctions are minimum. Objective: To establish fluid abuse postoperatively following minor and intermediate surgeries. Patients and Methods: This is a prospective study done in Iraq-Diyala-Baquba teaching hospital over a period of one year from January 2018 – January 2019.The case sheets of 640 elective surgical cases had been reviewed for the intravenous fluid prescription after surgery. The types of surgeries reviewed were those which theoretically based, do not need postoperative intravenous fluid administration or shouldn’t be given for more than few hours; but should start early oral fluid. The emergency cases were excluded from this study. The data collected from the case sheets of different elective surgeries in the surgical ward. The 640 patients who underwent elective mild to intermediate surgeries. Results: Of those who underwent surgeries under general anesthesia, it has been found that 288 out of 390 patients (90%) were given intravenous fluid postoperatively for a period from 8- 24 hours. Of those who underwent surgeries under spinal anesthesia, it has been found that 134 out of 174 patients (77%) patients were given intravenous fluid postoperatively for a period from 8- 12 hours. Of those who underwent surgeries under local anesthesia, it has been found that 36 out of 76 patients (47%) were given intravenous fluid postoperatively for a period from 8- 12 hours. The volume of fluid prescribed ranged from 500ml to 2 liters. Conclusion: Routine prescription of intravenous fluids following minor to intermediate surgeries is theoretically unsupported and is unnecessary most of the time as far as the patient is maintained well hydrated intraoperatively.